BUSINESS MANAGEMENT AND ITS INDIVIDUAL (Web of Teachers: Inderscience Research, 2024)
Nowadays, it is no secret that ideal business management is one of the greatest achievements. One of the most positive things to do is to help society and our loved ones by starting a profitable business as a result of business activity.